Exploring the Impact of Industry 4.0 on Logistics Management: Achieving Sustainable Competitiveness in the Contemporary Business Landscape - Masruroh, Masruroh; Irvianti, Laksmi Sito Dwi; Nursanti, Tinjung Desy; Nurrahma, Adynda; Mustikayani, Mustikayani; Yulnizar, Afreilya (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
The purpose of this study is to determine the fundamental factors that contribute to PT. X's competitive advantage. Utilizing Multi-ple Linear Regression Analysis, the data collected from 135 indi-viduals who participated in the survey at PT. X revealed significant conclusions. According to the findings of the study, the culture of an organization demonstrated a positive and considerable influence on the competitive advantage of the organization. Knowledge Shar-ing, on the other hand, was shown to be an essential contributor, demonstrating a positive and significant influence on Competitive Advantage at PT. X. Furthermore, the research revealed that Or-ganizational Innovation is still another crucial component, demon-strating that it has a positive and significant impact on Competitive Advantage. It is important to note that when taken into account as a whole, the three factors of Organizational Culture, Knowledge Sharing, and Organizational Innovation all showed a positive and significant impact on Competitive Advantage at PT. X. PT. X's competitive advantage can be improved through the synergistic in-fluence of culture, information exchange, and innovation, as high-lighted by these studies, which shed light on the subtle interplay of organizational factors.